Long-term dynamics of fire-affected pine-dipterocarp forest in Northern Thailand - RAPEEPORN KANTASRILA; JANJIRA MUENREW; WORANART THAMMARONG; NATCHA SUTJARITJAI; WIRATA RUJICHAIPIMON; SARAYUT RAKARCHA; WITTAYA PONGAMORNKUL; KRITTAPON MOOLLA; PRATEEP PANYADEE (Society for Indonesian Biodiversity, 2026)
Abstract. Kantasrila R, Muenrew J, Thammarong W, Sutjaritjai N, Rujichaipimon W, Rakarcha S, Pongamornkul W, Moolla K, Panyadee P. 2026. Long-term dynamics of fire-affected pine-dipterocarp forest in Northern Thailand. Biodiversitas 27 (2): d270211. https://doi.org/10.13057/biodiv/d270211. Fire disturbance is a critical ecological driver in Southeast Asian tropical forests, yet long-term empirical evidence of repeated fire regime remains limited. This study examined 13-year post-fire dynamics in a pine-dipterocarp forest using a 1-ha permanent plot at Queen Sirikit Botanic Garden, Northern Thailand. Trees with Diameter at Breast Height (DBH) ≥ 4.5 cm were monitored in 2012 and 2025, along with saplings (1.5-4.4 cm DBH) in the latter census. Species richness increased from 40 to 47 species, and basal area rose from 22.52 to 26.06 m² ha-¹, indicating structural recovery. Recruitment (1.63% yr-¹) exceeded mortality (1.15% yr⁻¹), suggesting demographic resilience. While dominant canopy species such as Pentacme siamensis, Quercus kingiana, Dipterocarpus obtusifolius, and Pinus kesiya persisted, the sapling layer was dominated by fast-growing deciduous species (Dalbergia suthepensis, Wendlandia tinctoria, and Lithocarpus sootepensis), indicating contrasting regeneration composition between life stages under repeated fire. Aboveground biomass increased from 135.57-159.21 to 148.05-173.62 t ha-¹ across allometries, with carbon stocks rising from 80.92-95.03 to 88.37-103.63 t C ha-¹. These results reflect net accumulation of biomass and carbon between 2012 and 2025 in the fire-affected forest. The study provides the first long-term evidence of demographic and carbon recovery in a fire-prone forest ecosystem in Thailand, underscoring the importance of permanent plot monitoring for adaptive fire management and climate change mitigation.